Kurikulum Merdeka dalam Perspektif Kajian Teori: Analisis Kebijakan untuk Peningkatan Kualitas Pembelajaran di Sekolah - Roos M. S. Tuerah; Jeanne M. Tuerah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article aims to conduct a policy analysis of the "Kurikulum Merdeka" (Independent Curriculum) from a theoretical perspective. Through the approach of policy analysis and relevant theoretical frameworks, this study examines the formulation and implementation of the Kurikulum Merdeka as an effort to improve the quality of learning in schools. In this policy analysis, we collect and analyze related policy documents, literature reviews, and relevant research findings to understand the policy's objectives, strategies employed, and its impact on the quality of learning. Our analysis identifies key factors that influence the success of the Kurikulum Merdeka, such as the role of teachers, structured curriculum, and community involvement. Additionally, we uncover implementation challenges faced in implementing the Kurikulum Merdeka and provide recommendations for its improvement and development. This research contributes to expanding our understanding of the Kurikulum Merdeka as an educational policy from a theoretical perspective and offers insights for education stakeholders to enhance the quality of learning in schools